A obra de Hermógenes Lima Fonseca e as culturas tradicionais do norte do Espírito Santo - Freitas, Bartolomeu Boeno de (2021)
The present study investigated the relevance of the literary work of Hermógenes Lima Fonseca and its relationship with the traditional cultural practices of the north of the State of Espírito Santo, focusing on the traditional Afro-Brazilian communities of the Sapê do Norte region, located between the counties of Conceição da Barra and São Mateus. The study sought to gather the set of this author's work and identify, in his narratives, elements characteristic of these traditional cultures, as well as to collaborate with the preservation of the work of the writer and cultural activist and contribute to the history of the cultural heritage of Espírito Santo. Hermógenes Lima Fonseca (1916-1996) was an intellectual and folklorist who devoted much of his life to the “mission” of researching, recording and disseminating the cultural practices of traditional communities in Espírito Santo. In the last years of his life, he gathered in books a set of chronicles, poetry, children's stories, among other literary texts that resulted from his activities, experiences and contacts with these communities. Hermógenes was an accountant, professor, politician, journalist and researcher. He was a member of the Espírito Santense de Folklore Commission, the Espírito Santense Academy of Letters and the Historical and Geographical Institute of Espírito Santo. Its legacy for the culture of Espírito Santo is widely recognized, both by official bodies, such as the State Government, Federal University of Espírito Santo and municipal governments, as well as by the participants of the different groups of traditional cultures in the State. The study collected testimonials from personalities who testify to the importance of his work and brings together several texts by the author in which characteristic elements of these traditional communities, their way of life, their devotions, struggles, knowledge and actions expressed in their cultural practices are present.